Impact of the COVID-19 Pandemic on Keratoplasty and Corneal Eye Banking. Issue 8 (August 2021) - Ballouz, Dena; Sawant, Onkar B.; Hurlbert, Susan; Titus, Michael S.; Majmudar, Parag A.; Kumar, Ashok; Zhou, Yunshu; Musch, David C.; Mian, Shahzad I.
Abstract : Purpose: The purpose of this study was to assess the impact of COVID-19 guidelines for corneal donor tissue screening and the utility of routine postmortem COVID-19 testing of donors intended for surgical use at a single eye bank. Methods: A retrospective analysis of referrals to and eligible donors from an eye bank between March 1, 2020, and June 30, 2020, was performed, with the same time period in 2019 as a control. Referrals who were not procured because of Eye Bank Association of America COVID-19 guidelines and eye bank–specific restrictions were noted. The results of 1 month of routine postmortem testing performed by the eye bank were examined. Analysis of variance tests were performed to assess the change between donors from 2019 to 2020. Results: There was a significant reduction in both the number of total referrals to the eye bank ( P = 0.044) and donors eligible for surgical transplantation ( P = 0.031). Eye Bank Association of America COVID-19 guidelines reduced the number of referrals over this period by 4% to 14%. Of the 266 surgically eligible donors who received postmortem COVID-19 testing in June by the eye bank, 13 resulted positive (4.9%). Conclusions: Despite a reduction in referrals and eligible corneal transplant donors at a single eye bank, there was a surplus of surgically suitable corneal tissue during the first wave of the COVID-19 pandemic. Eye banks should consider routine postmortem COVID-19 testing to identify asymptomatic infected donors although the risk of transmission of COVID-19 from infected donors is unknown. Abstract : Supplemental Digital Content is Available in the Text.